Hyperinsulinemic Hypoglycemia and Growth Hormone Deficiency Secondary to 20p11 Deletion - Erica Wee; John Herriges; Kavitha Dileepan; Sarah L. Tsai; Joseph T. Alaimo; Emily Paprocki (Case Reports in Endocrinology)
Hypoglycemia is concerning for neurological complications in infants and children. Determining the cause of hypoglycemia is essential in providing appropriate treatment. Hyperinsulinism and growth hormone deficiency are known causes of hypoglycemia but are not commonly found together. We report a 4-month-old boy who presented with severe hypoglycemia and was found to have both hyperinsulinism and growth hormone deficiency. Treatment with both recombinant human growth hormone and diazoxide led to blood glucose normalization. Subsequently, he was found to have a genetic diagnosis of 20p11.22p11.21 deletion. 20p11 deletions have been associated with hypopituitarism, most commonly seen in growth hormone deficiency causing hypoglycemia. This case is one of a few to report hyperinsulinism as a manifestation of this deletion.